Teknologi Artificial Intelligence dalam Evaluasi Pendidikan: Masa Depan Penilaian Pembelajaran - Marwela Remini Seo; Endi Tanaem; Omega Bia; Heldi Efraim Amung; Hemi Damnosel Bara Pa (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The information technology revolution has drastically changed the world of education, especially in the context of learning evaluation. The implementation of Artificial Intelligence (AI) offers an innovative solution to replace traditional assessment methods that are often unable to measure student competencies comprehensively. With real-time data analysis capabilities, AI can provide more personalized and adaptive assessments, helping students understand their learning process better. This study aims to explore the impact of AI on educational evaluation, identify benefits and challenges, and recommend best practices for AI integration. The method used is a literature review with a descriptive analytical approach, collecting various relevant studies to support the analysis. The results of the study indicate that AI has the potential to revolutionize the education evaluation system in Indonesia by increasing the accuracy and efficiency of assessments. However, challenges such as limited infrastructure and lack of educator competence remain a concern. Therefore, collaboration between the government, educational institutions, and industry is needed to create an adaptive and responsive learning ecosystem. With the right investment in AI technology, the future of learning evaluation is expected to be more accurate and effective, preparing students to face challenges in the digital economy era.